2003
DOI: 10.1007/s00431-002-1141-3
|View full text |Cite
|
Sign up to set email alerts
|

Small thymus at birth and neonatal outcome in very-low-birth-weight infants

Abstract: Acute thymic involution in the human fetus and newborn is associated with histological chorioamnionitis, a leading cause of prematurity, neonatal morbidity and mortality [3, 5,12,14]. Positive linear relationships between thymus size, birth weight [7] and gestational age [5] have been reported. Although a small thymus size at birth has been shown to be an accurate predictor for bronchopulmonary dysplasia (BPD) in very-low-birthweight (VLBW) infants [4], no information exists to date on the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…Cumulating evidence indicates that HCA is associated with a fetal inflammatory systemic response syndrome (4,11,46). Our research on acute thymic involution in newborns and fetuses with proven HCA is in line with this notion (22,(47)(48)(49). Although these data are suggestive of a similarity between the systemic inflammatory response syndrome of the fetus/ newborn and that seen in children and adults, to date no information exists on this intriguing issue.…”
Section: Discussionsupporting
confidence: 78%
“…Cumulating evidence indicates that HCA is associated with a fetal inflammatory systemic response syndrome (4,11,46). Our research on acute thymic involution in newborns and fetuses with proven HCA is in line with this notion (22,(47)(48)(49). Although these data are suggestive of a similarity between the systemic inflammatory response syndrome of the fetus/ newborn and that seen in children and adults, to date no information exists on this intriguing issue.…”
Section: Discussionsupporting
confidence: 78%
“…Fourthly, HCA is a leading cause of preterm birth [23,[25][26][27][28][29][34][35][36] and we have found an association between phthalate exposure and a shortened duration of pregnancy in humans [6].…”
Section: Discussionmentioning
confidence: 91%
“…Although suppression of COX-2 expression, mediated by PPARs, has been reported in various tissues and cell lines, some natural PPAR agonists induce cyclooxygenase (COX)-2 expression and activity, the enzyme catalyzing the rate-limiting step leading to the production of prostaglandins associated with labour within intrauterine tissues [14][15][16][17][18][19][20][21]. To this regard, COX-2 is induced during inflammation-mediated preterm labor [22] and it is believed to be overexpressed in chorioamnionitis (CA), a well known fetal systemic inflammatory response syndrome, and a leading cause of fetal/neonatal morbidity and mortality, including fetal death, preterm birth and brain injury [23][24][25][26][27][28][29][30][31][32][33][34][35][36]. On the other hand, EFAs play a critical role for fetal growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has shown the occurrence of an acute fetoneonatal thymic involution following a placental inflammatory process, as a result of a possible activation of the fetal and/or maternal hypothalamic-pituitaryadrenal axis in preterm labor and delivery (32)(33)(34)(35)(36)(37). To this regard, corticotropin releasing factor (CRF) placental receptors may play a major role in activation of the maternal and fetal hypothalamic-pituitary-adrenal axis.…”
Section: Discussionmentioning
confidence: 99%